WORKSHOP ON QRIS ADAPTATION AND SOCIAL MEDIA UTILIZATION FOR MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES) - Runtunuwu, Prince Charles Heston (Jurnal Gembira: Pengabdian Kepada Masyarakat, 2025)
The issue of digital economy in Indonesia should inevitably involve Micro, Small, and Medium Enterprises (MSMEs), which contribute significantly to national economic growth—accounting for as much as 61.07% of the country’s GDP. According to research data from the World Bank, approximately 80% of MSMEs that are connected to the digital ecosystem demonstrated stronger resilience during the pandemic. However, many MSMEs have not yet widely adopted or evenly implemented digital branding practices. The methodology applied in this study involved four data collection methods: observation, interviews, documentation, and triangulation/data validation. The outcomes of the workshop and training programs showed that participants received materials on branding and social media branding, as well as training in product photography to support their branding and promotion in the digital world. It is expected that with innovations such as QRIS, along with digital economy issues, social media digital branding, and product photography becoming shared national concerns, digitalization in Indonesia will continue to develop and support the country in becoming a developed nation. As a result of the training, MSME participants were able to understand the concepts of digital branding through social media and QRIS, and were capable of creating product photos to support their businesses.